2022
DOI: 10.1128/jmbe.00262-21
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Study of a Poster Presentation Activity, Students’ Science Identity, and Science Communication Self-Efficacy under Remote Teaching Conditions

Abstract: Disseminating and communicating scientific findings is an acknowledged part of the research experience, but few science programs include explicit undergraduate curricula for practicing oral science communication. Course-based undergraduate research experiences (CUREs) can provide opportunities for students to practice science communication, but few studies describe or assess authentic oral science communication activities within CUREs, and none do so under hybrid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…The results regarding the lowest self-efficacy in science communication may stem from a need for more experience in discussing the facts about science with students or people. This idea is supported by the findings of (Leone & French, 2022). They found that undergraduate students' science identity and science communication self-efficacy considerably increased after participating in a research experience as part of a course.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The results regarding the lowest self-efficacy in science communication may stem from a need for more experience in discussing the facts about science with students or people. This idea is supported by the findings of (Leone & French, 2022). They found that undergraduate students' science identity and science communication self-efficacy considerably increased after participating in a research experience as part of a course.…”
Section: Discussionmentioning
confidence: 69%
“…From this perspective, it is important to provide an opportunity to develop their competence, interest, and self-efficacies in science communication over their undergraduate and graduate teaching periods. Leone and French (2022) also revealed that undergraduate students had a higher self-efficacy in science communication after having experience teaching STEM subjects in the course. Based on this detail, a reason for students' lowest mean scores regarding their competence, interest, and self-efficacies in science communication may stem from their lack of experience during their university teaching STEM subjects to transmit them to the students and the public.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Literatürde çok sayıda araştırmacının (Arpacı, 2011;Ateş ve Saylan, 2015;Budiarti vd., 2022;Burns vd., 2021;Hasanah vd., 2021;Palmer, 2006;Saracaloğlu ve Yenice, 2009;Tschannen -Moran ve Woolfolk-Hoy, 2000) öz-yeterlikle ilişkili çalışmalar yaptığı görülmektedir. Öz-yeterliğin çeşitli değişkenlerle ilişkisi üzerine yapılan çalışmalar (Chen vd., 2022;Leone ve French, 2022;Saracaloğlu ve Aydoğdu, 2012;Yenice, 2012), akademik özyeterlik üzerine yürütülen araştırmalar (Bayraktar, 2009;Denizoğlu, 2008;Ekici, 2008;Küçükyılmaz ve Duban, 2006), öz yeterlilik ölçeği geliştirme çalışmaları (Bıkmaz, 2002;Ekici, 2009;Kiremit, 2006;Enochs ve Riggs, 1990) ve fen bilimlerine yönelik öz yeterlilik (Üredi ve Üredi, 2006;Küçükyılmaz ve Duban, 2006) Tarama modeli, özellikle yeni bir konuda araştırma yapmadan önce o alanda yapılan çalışmaları özetleyerek bir temel oluşturmak ve araştırmanın nereye doğru yöneleceğine karar vermek için sıklıkla kullanılır (Can, 2014;Karasar, 1998).…”
Section: Fen öğRetimi öZ Yeterlik İnancıunclassified